Step
*
of Lemma
dot-product-split
No Annotations
∀[n:ℕ]. ∀[k:ℕn]. ∀[x,y:ℝ^n].  (x⋅y = (x⋅y + λi.(x (k + i))⋅λi.(y (k + i))))
BY
{ ((Intros
    THEN (Assert λi.(x (k + i)) ∈ ℝ^n - k BY
                (All (Unfold `real-vec`) THEN Auto))
    THEN (Assert λi.(y (k + i)) ∈ ℝ^n - k BY
                (All (Unfold `real-vec`) THEN Auto)))
   THEN (Assert x ∈ ℝ^k BY
               (All (Unfold `real-vec`) THEN Auto))
   THEN (Assert y ∈ ℝ^k BY
               (All (Unfold `real-vec`) THEN Auto))
   THEN (Unhide THENA Auto)) }
1
1. n : ℕ
2. k : ℕn
3. x : ℝ^n
4. y : ℝ^n
5. λi.(x (k + i)) ∈ ℝ^n - k
6. λi.(y (k + i)) ∈ ℝ^n - k
7. x ∈ ℝ^k
8. y ∈ ℝ^k
⊢ x⋅y = (x⋅y + λi.(x (k + i))⋅λi.(y (k + i)))
Latex:
Latex:
No  Annotations
\mforall{}[n:\mBbbN{}].  \mforall{}[k:\mBbbN{}n].  \mforall{}[x,y:\mBbbR{}\^{}n].    (x\mcdot{}y  =  (x\mcdot{}y  +  \mlambda{}i.(x  (k  +  i))\mcdot{}\mlambda{}i.(y  (k  +  i))))
By
Latex:
((Intros
    THEN  (Assert  \mlambda{}i.(x  (k  +  i))  \mmember{}  \mBbbR{}\^{}n  -  k  BY
                            (All  (Unfold  `real-vec`)  THEN  Auto))
    THEN  (Assert  \mlambda{}i.(y  (k  +  i))  \mmember{}  \mBbbR{}\^{}n  -  k  BY
                            (All  (Unfold  `real-vec`)  THEN  Auto)))
  THEN  (Assert  x  \mmember{}  \mBbbR{}\^{}k  BY
                          (All  (Unfold  `real-vec`)  THEN  Auto))
  THEN  (Assert  y  \mmember{}  \mBbbR{}\^{}k  BY
                          (All  (Unfold  `real-vec`)  THEN  Auto))
  THEN  (Unhide  THENA  Auto))
Home
Index